AN ANALYSIS OF INSTRUCTIONAL PICTURES USED IN PRIMARY ENGLISH COURSEBOOKS - Sista Laksita Dewi; Harto Pramono (Widya Mandala Surabaya Catholic University, 2018)
This study analysed the types and roles of instructional pictures used in selected English coursebooks for elementary schools in Indonesia, and more specifically, the extent to which the pictures corresponded to the characteristics (principled set) of effective instructional pictures. Results of the analysis indicated that the type of pictures mostly belonged to less realistic type which was suitable for supporting the roles the pictures played in accompanying English words/text. The picture roles were mostly for introducing the meanings of new target words they accompanied, i.e., to support students’ comprehension of written text (target words) and for reinforcing and/or establishing the target words that had been introduced by accompanying varied activities represented through the written text (words), i.e., to enhance students’ retention of new target words. Most instructional pictures in the selected coursebooks were considered very effective to support their roles as they met the characteristics of effective instructional pictures (relevance, clarity, familiarity, suitability of picture type, and completeness of pictorial aspects). These findings suggest that selection of instructional pictures used to complement information presented in text should consider such aspects as suitability of types, roles, and characteristics of effective pictures in supporting their roles, in particular, for the purpose of enhancing English learning. Implications in developing and selecting instructional pictures are discussed.